Implementation of Republic Act 9593 (National Tourist Act) as Perceived by the Selected Residents of Dipolog City, Philippines - Batara, Abraham; Flora, Chrymae (JPAIR Multidisciplinary Research, 2017)
Tourism has provided some essential benefits to the local community as an economic development tool which paved the way for employment and investment, cultural attraction, festivals and outdoor reaction opportunities (Anderek & Vogt, 2000). The study was conducted to assess the implementation of Republic Act 9593 (National Tourist Act) as perceived by the selected residents of Dipolog City. Specifically, it determined: 1) the awareness of the residents of Dipolog City on the implementation of RA 9593; 2) the roles of the LGUs of Dipolog City on the implementation of RA 9593; and 3) the perceptions of the residents of Dipolog City on the effects of implementation of RA 9593 in terms of benefits and satisfaction. There are 100 respondents of this study from the five communities of Dipolog with 6 key informant officials. Frequency and percentage were used in the presentation and analysis of data collected through survey and interviews with key informants. Using descriptive method, results revealed that by implementing the policy of Tourism Act of 2009 in Dipolog, positive effects on the city economic, social and environmental development occurred. The awareness of the residents contributed successful implementation of Tourism Act of 2009, by formulating their own policies in the form of ordinances, resolutions, plans and programs of LGU units.